2022
DOI: 10.1136/archdischild-2021-323559
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of SARS-CoV-2 positivity in infants with bronchiolitis: a multicentre international study

Abstract: BackgroundBronchiolitis is the leading acute respiratory tract infection in infants during the winter season. Since the beginning of the SARS-CoV-2 pandemic, a reduction in the number of bronchiolitis diagnoses has been registered.ObjectiveThe present study aimed to describe the incidence and clinical features of bronchiolitis during the 2020–2021 winter season in a large cohort of children in Europe and Israel, and to clarify the role of SARS-CoV-2.Setting, patients, interventionsWe conducted a multicentre ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 31 publications
4
17
1
Order By: Relevance
“…The most frequent symptom was fever, followed by respiratory symptoms, such as a cough and mild breathing difficulties, as previously reported 3 . None of the virus positive infants developed bronchiolitis, in line with other data 4 . In fact, infants in the virus negative group were more likely to need intensive care for bronchiolitis and the respiratory syncytial virus, despite the dramatic decreases in these during the first year of the pandemic 5 …”
Section: Positive For Sars‐cov‐2 (N = 29) Negative For Sars‐cov‐2 (N ...supporting
confidence: 88%
See 1 more Smart Citation
“…The most frequent symptom was fever, followed by respiratory symptoms, such as a cough and mild breathing difficulties, as previously reported 3 . None of the virus positive infants developed bronchiolitis, in line with other data 4 . In fact, infants in the virus negative group were more likely to need intensive care for bronchiolitis and the respiratory syncytial virus, despite the dramatic decreases in these during the first year of the pandemic 5 …”
Section: Positive For Sars‐cov‐2 (N = 29) Negative For Sars‐cov‐2 (N ...supporting
confidence: 88%
“…3 None of the virus positive infants developed bronchiolitis, in line with other data. 4 In fact, infants in the virus negative group were more likely to need intensive care for bronchiolitis and the respiratory syncytial virus, despite the dramatic decreases in these during the first year of the pandemic. 5 Our study had some limitations.…”
mentioning
confidence: 99%
“…Despite the limitations, these data showed that, in children under two years of age with SARS-CoV-2 infection, respiratory symptoms are less severe compared to those observed in children with RSV infection or co-infection; in addition, SARS-CoV-2 infection is confirmed to be a less common cause of bronchiolitis compared to SARS-CoV-2. Surprisingly, despite what reported in the literature [ 7 ] our data showed that SARS-CoV-2 bronchiolitis is not mild. Our cohort of children with SARS-CoV-2-induced bronchiolitis showed a similar risk of a severe clinical course compared to children with bronchiolitis induced by RSV and co-infections.…”
Section: Discussioncontrasting
confidence: 99%
“…In our population, bronchiolitis was more frequently observed in the group of children with RSV infection 68/78 (87.1%) than in children with co-infection 9/13 (69.2%) or children with SARS-CoV-2 infection alone 10/47 (21.3%). This result agrees with data from the literature showing that bronchiolitis due to SARS-CoV-2 is less frequently observed than RSV-induced bronchiolitis is [ 7 ]. Despite this, the incidence in our population is still higher than that reported in the literature, also because the infections of our cohort originate from the Omicron rather than the Delta variant wave.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation